Developing a Module of Art Based Therapy for Behavior Modification In Mentally Challenged Children - Rane, Aushka; Malawade, Mandar (Journal of Neonatal Surgery, 2025)
Background: Art-Based Therapy (ABT) has gained attention as an effective intervention for improving social, emotional, and behavioral outcomes in mentally challenged children. This study explores its impact on social maturity. Objectives: The primary objective was to develop and evaluate a structured ABT module incorporating colors, music, and drama to enhance social maturity in mentally challenged children aged 0–18 months. Methodology: A total of 20 participants underwent ABT sessions three times a week for six weeks. The intervention targeted social maturity, with pre and post-intervention assessments conducted using the Vineland Social Maturity Scale (VSMS). Statistical analysis was performed to evaluate the intervention's effectiveness, including effect size calculations. Results: The study demonstrated a significant improvement in VSMS scores post-intervention (p < 0.001). The effect size was large (Cohen’s d = 3.53) with a strong correlation (r = 0.97), indicating substantial positive outcomes. Conclusion: The findings suggest that ABT is an effective intervention for improving social maturity in mentally challenged children, highlighting its potential as a valuable therapeutic approach in behavior modification strategies. Further research with larger samples and long-term follow-ups is recommended.